The handbook of survival at sea - Beeson, Chris (Grannge Books, 2003)
How would you cope if you fond yourself isolated miles from civilization? Would you have the necessary tools to survive? Unless they had received some level of military training most people would struggle badly if faced with such scenario, but imagine if the terrain was water and you were stranded in the middle of one of the world's oceans. The Handbook of Survival at Sea confronts this daunting scenario head-on and offers the reader a variety of solutions to overcome the hardships that any survivor would inevitably face. This book is packed with practical information and insight tips such as how to avoid burning oil on the surface of the water, how to construct your own raft, how to minimize the risks of shark attacks, and how to make unpalatable seawater safe for drinking. Being stranded at sea is a terrifying experience, but one that everyone should be prepared for. Weather you are an unfortunate victim of a shipwreck or have merely become disorientated during an afternoon's sailing, this book, crammed with essential tips, will be your best chance of survival.